Cortical Plasticity After Surgical Tendon Transfer in Tetraplegics - Wester, Knut; Hove, Leiv M.; Barndon, Roger; Craven, Alexander R.; Hugdahl, Kenneth (Frontiers in Human Neuroscience, 2018)
Background. Developmental cortical plasticity with reorganization of cerebral cortex, has been known to occur in young and adult animals after permanent, restricted elimination of afferent (visual or somatosensory) input. In animals, cortical representation of unaffected muscles or sensory areas has been shown to invade the neighboring cortex when this is deprived of its normal sensory input or motor functions. Some studies indicate that similar cortical plasticity may take place in adult humans. Methods. In patients with a high cervical spinal cord injury leaving the patient without any movements of the fingers, we performed fMRI studies of the cortical representation of an elbow flexor muscle before and after a surgical procedure that changed its function to a thumb flexor, thus providing the patient with a useful grip. Results. Preoperatively, the elbow flexion movement was elicited from a cortical area corresponding with the “elbow area” in healthy individuals. Despite the fact that an elbow flexor was used for the post-operative key-grip, this movement in the tetraplegic patients was elicited from a similar brain region as in healthy controls (the “hand area”). This supports our hypothesis that control of that muscle shifts from a brain region typically associated with elbow movement, to one typically associated with wrist movements. Conclusions. The findings presented here show with fMRI that the human cortex is capable of reorganizing itself spatially after a relatively acute change in the periphery.